The Initiation Factors eIF2, eIF2A, eIF2D, eIF4A, and eIF4G Are Not Involved in Translation Driven by Hepatitis C Virus IRES in Human Cells - González-Almela, Esther; Williams, Hugh; Sanz, Miguel A.; Carrasco, Luis (Frontiers in Microbiology, 2018)
Animal viruses have evolved a variety of strategies to ensure the efficient translation of their mRNAs. One such strategy is the use of internal ribosome entry site (IRES) elements, which circumvent the requirement for some eukaryotic initiation factors (eIFs). Much effort has been directed to unravel the precise mechanism of translation initiation by hepatitis C virus (HCV) mRNA. In the present study, we examined the involvement of several eIFs in HCV IRES-driven translation in human cells in a comparative analysis with mRNAs bearing the encephalomyocarditis virus or the Cricket paralysis virus IRES element. Consistent with previous findings, several inhibitors of eIF2 activity, including sodium arsenite, thapsigargin, tunicamycin and salubrinal, had no inhibitory effect on the translation of an mRNA bearing the HCV IRES, and all induced the phosphorylation of eIF2α. In addition, hippuristanol and pateamine A, two known inhibitors of eIF4A, failed to block HCV IRES-directed translation. To test the release of nuclear proteins to the cytoplasm and to analyze the formation of stress granules, the location of the nuclear protein TIA1 was tested by immunocytochemistry. Both arsenite and pateamine A could efficiently induce the formation of stress granules containing TIA1 and eIF4G, whereas eIF3 and eIF2 failed to localize to these cytoplasmic bodies. The finding of eIF4A and eIF4G in stress granules suggests that they do not participate in mRNA translation. Human HAP1 cells depleted for eIF2A, eIF2D, or both factors, were able to synthesize luciferase from an mRNA bearing the HCV IRES even when eIF2α was phosphorylated. Overall, these results demonstrate that neither eIF2A nor eIF2D does not participate in the translation directed by HCV IRES. We conclude that eIF2, eIF4A, eIF2A and eIF2D do not participate in the initiation of translation of HCV mRNA.